Genetic evaluation of performance traits in Brazilian Quarter Horse - Monteiro Correa, Marcio Jose; da Mota, Marcilio Dias Silveira (Polish Academy of Sciences, Institute of Plant Genetics, 2007)
The aim of this study was to estimate genetic parameters for racing performance traits in Quarter Horses in Brazil. The data (provided by the Sorocaba Jockey Club) came from 3 Brazilian hippodromes in 1994-2003, with 11875 observations of race time and 7775 of the speed index (Sl), distributed in 2403 and 2169 races, respectively. The variance components were estimated by the MTGSAM program, under animal models including the random additive genetic effect, random permanent environmental effect, and the fixed effects of sex, age and race. Heritabilities for race time and the SI, for the 3 distances studied (301, 365 and 402 in), varied from 0.26 to 0.41 and from 0. 14 to 0. 19, respectively, whereas repeatabilities varied from 0.36 to 0.68 (time) and from 0.27 to 0.42 (SI) and the genetic correlations from 0.90 to 0.97 (time) and from 0.67 to 0.73 (SI).
Keywords: horse; Gibbs sampling; racing performance